Dr Prosa Sunda Sebagai Media Pendidikan Tafsir: Resepsi al-Quran dalam Carpon dan Esei Karya E. Abdurrahman : Resepsi al-Quran dalam Carpon dan Esei Karya E. Abdurrahman - Roni Nugraha (UIN Sunan Gunung Djati Bandung, 2026)
This study examines Sundanese prose as a medium for Qur’anic education, focusing on the reception of the Qur’an in the carpon (short stories) and essays of E. Abdurrahman. The findings reveal that E. Abdurrahman integrates Qur’anic values into narrative elements—such as plot, setting, dialogue, and everyday situations—bringing the Qur’anic text closer to readers’ lived experiences. His Qur’anic carpon and essays function not only as cultural exegesis but also as an educational medium for Qur’anic interpretation, encompassing moral, spiritual, social, and political dimensions. These works can be positioned as a form of cultural exegesis that synthesizes religiosity, aesthetics, and local consciousness. Thus, literature serves as a productive space for creative reception of the Qur’an, contributing to the development of a more inclusive, communicative, and contextual framework for Qur’anic learning in the Nusantara (Southeast Asian) context.